Circulating monocytes from prostate cancer patients promote invasion and motility of epithelial cells. (9th August 2018) - Cavassani, Karen A.; Meza, Rebecca J.; Habiel, David M.; Chen, Jie‐Fu; Montes, Alexander; Tripathi, Manisha; Martins, Gislâine A.; Crother, Timothy R.; You, Sungyong; Hogaboam, Cory M.; Bhowmick, Neil; Posadas, Edwin M.
Abstract: Background: Recruited myeloid cells are known to promote cancer initiation, malignant progression, metastasis, and resistance to therapy in the tumor niche. We tested the hypothesis that circulating blood monocytes from advanced prostate cancer (PCa) patients exhibit a protumor phenotype and directly influence the tumor microenvironment in response to tumor‐derived signals. Methods: Blood monocytes from advanced and stable PCa patients were cultured, and the conditioned media (CM) were collected and analyzed using standard invasion and wound closure assays to measure effects on invasion and motility of PCa tumor cells. We then identified the proteome profile of these monocytes using proteome array and ELISA. Results: Conditioned media from circulating monocytes in patients with metastatic prostate cancer (PCa‐M) increased invasion of epithelial PCa cells in vitro . Proteome Profiler Analysis revealed that monocyte‐derived CM from metastatic castration‐resistant (mCRPC) patients presented high levels of chitinase‐3‐like 1 (CHI3L1, YKL‐40) when compared to patients with stable disease (PCa‐N) and healthy control individuals (HC). The only described receptor for CHI3L1, interleukin‐13 receptor α2 (IL‐13Rα2), was significantly up‐regulated in the human metastatic PCa cell line, ARCaPM . Accordingly, we observed that the activation of IL‐13Rα2 from PCa‐M CM increased the invasiveness of ARCaPM cells while siRNA directed against this receptor significantly reduced invasiveness of these cells in the presence of CM from PCa‐M patients. Conclusions: Thus, we show that circulating monocytes from metastatic PCa patients exert a tumor‐promoting role via the secretion of CHI3L1, and CHI3L1 demands further exploration as a possible therapeutic target in advanced PCa. Abstract : Recruited myeloid cells promote cancer initiation, malignant progression, metastasis, and resistance to therapy in the tumor microenvironment. Herein, we report that conditioned medium (CM) from circulating monocytes in patients with PCa/mCRPC increased motility and invasion of epithelial PCa cells.